1978
DOI: 10.1128/aac.13.2.234
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of the Mode of Action of Streptolydigin in Escherichia coli: Induction of Transcription Termination In Vivo

Abstract: Growth of the permeable strain AS19 of Escherichia coli B is more sensitive to the antibiotic streptolydigin than is in vitro ribonucleic acid (RNA) synthesis. The in vivo chain elongation rates of lacZ messenger RNA and ribosomal RNA are not affected at 1.5 x 10-6 M, a concentration that reduces the growth rate threefold. The synthesis of large proteins is inhibited preferentially, and a considerable fraction of the polypeptides synthesized is unstable. The synthesis of complete ,8-galactosidase is inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Similarly, biochemical approaches showed that the elongation inhibitor streptolydigin freezes the transcription complex on the DNA template with the RNA product still bound. However, streptolydigin apparently causes rapid, complete and irreversible loss of transcription complexes in vivo (Von Meyenburg et al ., 1978), suggesting that some system(s) exists within the cell to dislodge the frozen RNA polymerase complexes, as we are proposing here for both streptolydigin and DPCs.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, biochemical approaches showed that the elongation inhibitor streptolydigin freezes the transcription complex on the DNA template with the RNA product still bound. However, streptolydigin apparently causes rapid, complete and irreversible loss of transcription complexes in vivo (Von Meyenburg et al ., 1978), suggesting that some system(s) exists within the cell to dislodge the frozen RNA polymerase complexes, as we are proposing here for both streptolydigin and DPCs.…”
Section: Discussionmentioning
confidence: 99%
“…This repression is reversed by the addition of DNA-binding agents (e.g., proflavin, norharman, and netropsin), which presumably inhibit the rate of transcriptional elongation (R. J. Neill, Ph.D. thesis, University of California, Berkeley, 1979). In a hisP' strain of S. typhimurium, sublethal concentrations of streptolydigin, which is an inhibitor of transcriptional elongation (33,38), preferentially stimulate pyrB expression (C. L. Turnbough, Jr., unpublished data). These results suggest that the expression of pyrA and pyrB is regulated by the relative rates of transcription and translation presumably of a leader DNA sequence immediately preceding the structural genes.…”
Section: Discussionmentioning
confidence: 99%
“…1) is an inhibitor of bacterial RNA polymerase ␤-subunit produced by Streptomyces lydicus (27,29) and a potent inhibitor of eukaryotic DNA polymerase terminal deoxynucleotidyltransferase (6,7). The streptolydigin biosynthetic gene cluster has been isolated and characterized from the producer organism (21).…”
mentioning
confidence: 99%